Evaluation of the Mucoadhesive Properties of Chitosan-Based Microstructured Lipid Carrier (CH-MLC) - Marta Guerini; Giorgia Condrò; Paola Perugini (MDPI AG, 2022)
Different mucoadhesive systems have been studied in recent years to increase the residence time of the delivery systems and to prolong the release of the drug. The aim of this work was to evaluate the mucoadhesive properties of chitosan-based Microstructured Lipid Carrier (CH-MLC) with a new approach which requires chitosan and mucin to be compacted into a tablet and mucoadhesion to be assessed on a non-mucoadhesive substrate. This type of test showed that chitosan maintains a close bond with mucin even in the presence of a fluid and even encapsulated in microparticles. After this, using a bioreactor, the release of N-acetylcysteine (NAC) from the microparticles (NA-CH-MLC) through a layer of mucus mimicking the pathological conditions of a patient with cystic fibrosis was tested. The release of the active from NAC-CH-MLC demonstrated how the chitosan inside the microparticles acts as a penetration enhancer and how the microparticles can impart a prolonged release over time.